Description Of Mother's Knowledge Levels Of Nutritional Status In Tolls In Nagari Tanjung Bungo, Suliki District, Lima Puluh Kota District - chyka febria (Journal of Midwifery, 2022)
In 2018 in West Sumatra, data on children under five who experienced malnutrition according to (BB/U) was 3.51% malnourished, undernourished 15.42%, well-nourished 79.46%, over-nourished 1.61%, based on prevalence nutritional status according to (TB/U) very short 9.66%,short 10.48%, and normal 79.86%. Nutritional status based on (W/U) in children under five in the District of Lima Puluh Kota, poor nutrition 2.12%, undernutrition 16.22%, and good nutrition 81.67%. According to the prevalence of nutritional status (TB/U) very short 10.78%, short 29.35%,and normal 59.87%. The purpose of this study was to determine the characteristics of the mother's level of knowledge about the nutritional status of toddlers. This type of research is descriptive which was carried out inKenagarian Tanjung Bungo, Suliki District, Lima Puluh Kota Regency with a total sample of 63 respondents. The results showed that the mother's level of knowledge was mostly in the high category with a total of 35 people (55.5%). The limitation of this study is that the researcher could not make direct observations about the mother's knowledge about the nutritional status of children under five. Researchers can only find out the mother's level of knowledge with the results of the questionnaire that has beendistributed to the respondents.